Supervision methods in tooth brushing by mothers on their children in relation to the caries rate among the mothers and their children - Mohd Kenali, Norzaiti; Maw, Tin; Mohd Yusof, N. A.; Nor Shakiman, N. B. (Elsevier, 2019)
Children aged 6 and below need supervision by their parents during tooth brushing. 40 children aged 4 and 5 together with their mothers were selected from IIUM Educare, Kuantan. They were assessed clinically for their caries status by using DMFT/dmft index. 57.5% of the mothers supervised their children during tooth brushing. Methods of supervision include; assisting the child during tooth brushing (22.5%), the mothers brush for the children once daily (22.5%) and the mothers brush for the children twice daily (12.5%). Interestingly, majority of the children who were caries free and have high caries rate did not receive any supervision. There was no significant relationship between methods of supervision and the caries status of the children (p value=0.905) and no correlation between caries status of the mothers and their children (r = 0.267, p value=0.096). This study concluded that supervision during child tooth brushing alone does not affect the caries status of the children.